The associations between lifestyle factors and mental well‐being in baccalaureate nursing students: An observational study. (8th February 2022) - Lee, Charlotte T.; Ting, Grace K.; Bellissimo, Nick; Khalesi, Saman
Abstract: Lifestyle factors are modifiable habits that shape the way in which individuals live their lives and can influence mental health. This study examined the associations between lifestyle factors and mental well‐being among baccalaureate nursing students at one Canadian university. A cross‐sectional, observational online survey was distributed at one urban university campus in Ontario, Canada. Baccalaureate nursing students ( n  = 147) completed the survey containing questions for demographic variables, sleep quality, dietary pattern, alcohol use, physical activity, sitting time, cigarette smoking, depression, anxiety and stress. Linear regression analysis revealed that more sitting time, poor sleep quality, and low dairy consumption were associated with higher scores in depression, anxiety, and psychological stress. In conclusion, poor lifestyle behaviors such as sedentary lifestyle, poor sleep, and low dairy consumption may reduce the mental well‐being of baccalaureate nursing students. Future efforts should aim to establish a causal relationship between lifestyle and mental well‐being, which would contribute to the development of lifestyle interventions to promote mental health.